(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Indian banking sector is facing a serious problem ofNPA. The magnitude of NPA is comparatively higher in public sectors banks. Toimprove the efficiency and profitability of banks the NPA need to be reducedand controlled. NPAs have been fighting cyclical movement or dieses on weekpatient and it is an underdevelopment feature like chronic poverty. This paperdeals with understanding the concept of NPAs, its magnitude and major causesfor an account becoming non-performing and strategies for managing NPA inIndian banks. The best indicator for the health of the banking industry in acountry is its level of Non-performing assets (NPAs). NPAs are one of the majorconcerns for banks in India. It reflects the performance of banks. Reduced NPAsgenerally gives the impression that banks have strengthened their creditappraisal processes over the years and growth in NPAs involves the necessity ofprovisions, which bring down the overalls profitability of banks.